MAIN ASPECTS OF INVESTMENT APPEAL OF SANATORIUM-RESORT SPHERE - Кристина Игоревна Беляева (Sovremennye Issledovaniâ Socialʹnyh Problem, 2013)
The purpose of the article consist in analysis of the main aspects of the investment attractiveness of the sanatorium resort institutes, exactly in marketing tools and techniques usage. The author has studied and systematized marketing tools which will increase the investment attractiveness of sanatoriums activity. The results of research can be used by enterprises of sanatorium-resort complex and in the educational process in disciplines basics of marketing, strategic marketing, marketing in sectors and activities. DOI: http://dx.doi.org/10.12731/2218-7405-2013-9-35